Pengaruh Kepemimpinan dan Kualitas Kerja terhadap Prestasi Kerja Personel Polri pada Densus 88 At Bidang Ditidensos Mabes Polri - Antoni, Jadi (Business Perspective Journal, 2025)
Leadership is expected to be able to mobilize all components and regulate the actions of all members in the organization. Work quality is a result that can be measured by the effectiveness and efficiency of a job. Work performance is the result of work achieved by someone in carrying out the tasks assigned to him. The purpose of the study is as follows: To determine whether together the influence of Leadership and Work Quality on the Work Performance of Police Personnel at Densus 88 AT, Ditidensos Division, National Police Headquarters.The sampling technique used in this study, the author used the Random Sampling technique or randomly from the existing population of 89 Police Personnel who were sampled referring to the Slovin formula in Husein Umar, 2017, 48 samples were obtained. Based on the results of the analysis of the positive influence of Leadership on the Work Performance of Police Personnel, a partial value of 0.925 is obtained, meaning there is a very strong influence or influence with a coefficient of determination of 83.6%. This is proven by the hypothesis test of the Leadership variable on the Work Performance of Police Personnel, the value of to = 8.701> t0.05 (46) = 1.681 is obtained, so Ho is rejected and Ha is accepted, meaning there is a very significant influence. Based on the results of the calculation, there is a positive influence of Work Quality on the Work Performance of Police Personnel, the partial value of 0.859 is obtained, meaning there is a very strong influence or influence with a coefficient of determination of 73.8%. This is proven by the hypothesis test of the Work Quality variable on the Work Performance of Police Personnel, the value of to = 4.575> t0.05 (46) = 1.681 is obtained, so Ho is rejected and Ha is accepted, meaning there is a significant influence. Simultaneously, the positive influence of the Leadership and Work Quality variables on the Work Performance variable of the Police Personnel with a simultaneous correlation value or Summary Model produces an R value of 0.950 and while the R Square value is 0.902 or 90.2%, this can be stated that the results of the analysis together the Leadership and Work Quality variables on the Work Performance variable of the Police Personnel have a very strong influence. Proven through the results of the F test (ANOVA) or F count obtained a value of 207.133 which is greater than Ftable (47) of 2.800 with a significant level of 0.000 because 0.000 <0.05, then it can be said that the Leadership and Work Quality variables together or simultaneously on the Work Performance of the Police Personnel have a very significant influence. Keywords: leadership, work quality and work performance of police personnel